Public Relations Management in Enhancing School Branding at Madrasah Tsanawiyah Jombang - Sunardi Sunardi; Ramadan Sahendra; Muhammad Aman Ma’mun; Mufarikha Binti Syarkun (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study explores the role of public relations management in enhancing school branding at MTsN 6 Jombang, focusing on its supporting and inhibiting factors. The research findings indicate that effective public relations strategies, such as optimizing information dissemination, fostering strong relationships with stakeholders, and promoting the school’s achievements, have significantly contributed to strengthening the institution’s image. The supporting factors include the commitment of the school leadership, active collaboration among teachers and staff, and the utilization of digital platforms for promotion. Meanwhile, the inhibiting factors comprise limited resources, insufficient public awareness, and certain technical constraints in implementing promotional programs.The scientific contribution of this research lies in providing a conceptual and practical framework for implementing public relations management in the educational sector, particularly in enhancing school branding in madrasah environments. Additionally, this study enriches the literature on educational management by presenting an integrated model that combines promotional strategies with community engagement. However, this research has limitations, such as its focus on a single institution, which may affect the generalizability of the findings. Future studies are recommended to involve multiple schools or madrasahs with different characteristics to obtain more comprehensive and comparative results. Broader exploration could also examine the long-term impact of public relations management on school competitiveness and sustainability.